2020
DOI: 10.3390/polym12020306
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organic Material Induced by Electron Beam Irradiation for Medical Application

Abstract: This study analyzed the effects of irradiation of polytetrafluoroethylene (PTFE) containing 40% of bronze using an electron beam with energy of 10 MeV. Dosages from 26 to156 kGy (2.6–15.6 Mrad) were used. The impact of a high-energy electron beam on the thermal, spectrophotometric, mechanical, and tribological properties was determined, and the results were compared with those obtained for pure PTFE. Thermal properties studies showed that such irradiation caused changes in melting temperature Tm and crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, Dadbin et al (2010) studied the effect of irradiation on molecular weight of PTFE and reported that on increasing the dose form 100 kGy to 500 kGy, the molecular weight of PTFE reduces. Similar trends were also reported by Barylski et al (2020), Barylski et al (2020).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, Dadbin et al (2010) studied the effect of irradiation on molecular weight of PTFE and reported that on increasing the dose form 100 kGy to 500 kGy, the molecular weight of PTFE reduces. Similar trends were also reported by Barylski et al (2020), Barylski et al (2020).…”
Section: Resultssupporting
confidence: 90%
“…The 10 mg of irradiated or pre-sintered PTFE scrap were analysed under nitrogen atmosphere at a flow rate of 20 cm 3 /min and at a heating rate 10°C/min up to 380°C. The average molecular weight of PTFE was calculated by using Suwas’ equation as follows (Dadbin et al , 2010; Barylski et al , 2020; Barylski et al , 2020). …”
Section: Experiments Methodologymentioning
confidence: 99%
“…Current research is focused on irradiation of pure polytetrafluoroethylene with gamma rays due to the availability of this type of source, while sources enabling electron radiation with sufficient energy to penetrate the material to a depth of few cm are less common [20]. In the previous paper by these authors [23,24], results similar to Khatipov's team data were obtained for a high-energy beam of electrons at room temperature. The aim of this study was to investigate the result of an increase in graphite content to 20% and radiation with a 10 MeV electron beam energy on mechanical, sclerometic and tribological properties of modified PTFE.…”
Section: Introductionmentioning
confidence: 92%
“…Graph showing the how the rates of polymer cross-linking and main chain scission interact to change the molecular weight of the polymer as electron dose is accumulated. Ultrahigh molecular weight polyethylene (UHMWPE) predominantly cross-links, while polytetrafluoroethylene (PTFE) degrades relatively quickly, and nylon-6,6 with its G (S): G (X) value close to one showing initial cross-linking and subsequent degradation with accumulating dose . UHMWPE data was adapted with permission from ref .…”
Section: Chemistry and Characterization Of E-beam Polymersmentioning
confidence: 99%
“…UHMWPE data was adapted with permission from ref . Nylon-6,6 data was adapted from ref . PTFE bronze data was adapted with permission from ref .…”
Section: Chemistry and Characterization Of E-beam Polymersmentioning
confidence: 99%